Enforcement of Mouthguard Use and Athlete Compliance in National Collegiate Athletic Association Men's Collegiate Ice Hockey Competition - Hawn, Kristen L. (National Athletic Trainers Association, 2002)
Objective: To determine enforcement patterns and athlete compliance with the National Collegiate Athletic Association (NCAA) rule requiring the wearing of mouthguards in men's collegiate ice hockey games during a single competitive season. Design and Setting: We developed a questionnaire and sent it to certified athletic trainers (ATCs) directly responsible for men's varsity collegiate ice hockey at 127 NCAA-affiliated institutions. Then χ(2) analyses were conducted to determine whether significant differences existed in the pattern of responses by division of play (Division I, II, or III or independent). Subjects: A total of 104 ATCs responded. We obtained data from 94 questionnaires with complete answers to primary questions addressing program enforcement of the rule and mouthguard use. Measurements: Our questionnaire asked about types of mouthguards used, attitudes of the sports medicine and coaching staffs regarding the role of mouthguards in prevention of injury, enforcement of mouthguard use, and actual numbers of athletes wearing mouthguards in competition. Respondents also provided an estimate of the number of penalties assessed against their team for mouthguard violations during the previous season. Results: Most ATCs (93%) reported that they believed mouthguards play a role in injury prevention. Respondents indicated someone on the coaching or sports medicine staff enforced the rule at 74% of the institutions, with a trend toward greater enforcement at the Division II and III levels. Overall, ATCs reported 63% of athletes consistently wore mouthguards in competition, with significantly higher compliance at the Division II and III levels. A total of 19 penalties were reportedly assessed for violation of the mouthguard rule the previous season. Conclusions: Our data suggest that the use of mouthguards in competition is not consistently enforced by ATCs, coaches, or game officials and that mouthguards are not routinely worn by athletes. These results raise legitimate concerns for all physicians, athletic trainers, coaches, and governing bodies involved with men's collegiate ice hockey.